The Quantified Brain: A Framework for Mobile Device-Based Assessment of Behavior and Neurological Function - Stark, David E.; Kumar, Rajiv B.; Longhurst, Christopher A.; Wall, Dennis P. (Applied Clinical Informatics, 2016)
Citation: Stark DE; Kumar RB; Longhurst CA; Wall DP. The Quantified Brain: A Framework for Mobile Device Based Assessment of Behavior and Neurological Function.